Economic injury level for Neohydatothrips signifer (Thysanoptera: Thripidae) in passion fruit at the Huila region, Colombia - SANTOS A., OSCAR; VARÓN D., EDGAR HERNEY; GAIGL, ANDREAS; FLORIANO, ANDREA (Revista Colombiana de Entomología, 2012)
Passion fruit is an important agricultural crop for the Huila region in Colombia. The thrips and specifically Neohydatothrips signifer, is the most important pest of this crop, causing extensive damage with inherent high econom- ic losses. One of the ways to rationalize the use of insecticides for its control is by treating based on an Economic Injury Level (EIL), using a related criterion, called Action Threshold (AT). The objective of this research was to determine the EIL for N. signifer, in a passion fruit crop at the Huila region. This study was carried out at the municipality of Suaza (Huila). A Complete Randomized Blocks design was established in order to measure the response of the passion fruit crop yield to increasing infestation levels (7, 14 and 21 thrips per meristem). A significant negative relationship between the infestation level and the yield was found, with the resulting equation being Y = 6768.4 - 311.34x. Using the func- tion: yield loss vs. thrips population levels, an EIL was calculated at 13 thrips/meristem. Also, two ATs were calculated, 10 thrips/meristem for normal temperature periods (22-27°C) and six thrips/meristem for higher temperature periods (28-35°C). These established criteria are the first step to the rational management of thrips in passion fruit in Colombia.